Reducing the False-Positive Rate for Isovalerylcarnitine in Expanded Newborn Screening - Sara Poggiali BSc, MT (Journal of Inborn Errors of Metabolism and Screening, 2016)
The isodecyl neopentanoate is an ingredient used in the cosmetic industry to prepare a nipple fissure balm. We report on 12 newborns that showed elevated C5-acylcarnitine levels upon newborn screening following treatment with balm. The first 3 neonates were immediately recalled for confirmatory tests and resulted negative for both isovaleric acidemia and short/branched chain acyl-CoA dehydrogenase deficiency. In the other 9 cases, the immediate recall was avoided by applying a new second-tier test able to confirm the presence of pivaloylcarnitine. The concentration of C5-acylcarnitine was measured in the days following the suspension of balm application. Abnormal concentrations of C5-acylcarnitine did not seem to be associated with free carnitine deficiency, probably due to the short time of exposure. A direct correlation between balm ingestion and the elevation in pivaloylcarnitine has been demonstrated in 10 adult volunteers. The commercial balm containing a pivalic acid derivative is causal of false-positive results during newborn screening, and it could have the potential to cause secondary carnitine deficiency when used chronically.